Аналіз ведення інстаграм-сторінки для просування особистого бренду тату-майстра - Мещерякова, А. В. (ХНУРЕ, 2024)
This work is aimed at considering the characteristics of the Instagram page and promotion of the tattoo artist's brand. The main elements of filling the page and the stages of their creation are described. The visual component of the account was analyzed, shortcomings and recommendations for their elimination were identified. Based on the analysis of the account, suitable methods for improving the content and filling the page are outlined. The most profitable brand promotion tools have been chosen to attract more audiences and customers.
Keywords: просування особистого бренду; інстаграм-сторінка